THEORETICAL APPROACHES TO DETERMINE THE EFFECT OF TEMPERATURE OF STORAGE OF FRUITS AND VEGETABLES AT THE RATE OF BIOCHEMICAL REACTIONS - Nicholas Grigorievich Scheglov (Современная наука и инновации)
The article discusses the theoretical basis and practical experience of the effect of temperature on the rate of biochemical reactions during storage of fruits and vegetables. The results obtained accurately reflect the effect of temperature on the rate of chemical reactions and explain why a slight increase in the temperature of the raw material during storage leads to such a drastic reduction in the duration of its storage.